2008
DOI: 10.1007/s10637-008-9113-8
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of Irofulven in combination with various anti-metabolites, enzyme inhibitors, and miscellaneous agents in MV522 lung carcinoma cells: marked interaction with gemcitabine and 5-fluorouracil

Abstract: The novel agent Irofulven (HMAF, NSC 683863) has demonstrated significant antitumor activity against solid tumors in various xenograft models and human clinical trials. The antitumor potential of combining irofulven with 72 different anti-metabolite, enzyme inhibiting, and miscellaneous agents was investigated in this study. The human lung carcinoma MV522 cell line and its corresponding xenograft model were used to evaluate the activity of irofulven in combination with these different agents. Irofulven in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…When NER was inhibited, the cells were 2-fold more sensitive toward AF, indicating that when the cell cannot remove the AF-adduct, cytotoxicity is promoted. This observation is in agreement with previous studies where it was demonstrated that NER-deficient cells were more sensitive to AF, suggesting that the associated DNA damage is an NER substrate. ,, Furthermore, in a previous screening study, UCN-01 was among a group of miscellaneous compounds that showed evidence of a synergistic effect with HMAF . These data are consistent with the notion that when treating cancer cells with a combination of UCN-01 and AF, the concentration of the cytotoxic drug can be lower to achieve the same effect as when treating solely with AF.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…When NER was inhibited, the cells were 2-fold more sensitive toward AF, indicating that when the cell cannot remove the AF-adduct, cytotoxicity is promoted. This observation is in agreement with previous studies where it was demonstrated that NER-deficient cells were more sensitive to AF, suggesting that the associated DNA damage is an NER substrate. ,, Furthermore, in a previous screening study, UCN-01 was among a group of miscellaneous compounds that showed evidence of a synergistic effect with HMAF . These data are consistent with the notion that when treating cancer cells with a combination of UCN-01 and AF, the concentration of the cytotoxic drug can be lower to achieve the same effect as when treating solely with AF.…”
Section: Discussionsupporting
confidence: 92%
“…10,23,24 Furthermore, in a previous screening study, UCN-01 was amongst a group of miscellaneous compounds that showed evidence of a synergistic effect with HMAF. 34 These data are consistent with the notion that when treating cancer cells with a combination of UCN-01 and AF, the concentration of cytotoxic drug can be lower to achieve the same effect as when treating solely with AF. Translated to therapeutic applications, this property might result in fewer side-effects.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, the cytotoxicity of these drugs depends on an intact DNA repair pathway. Irofulven has also been shown to synergize with cisplatin and gemcitabine , both in in vitro and in vivo tumor models. Thus, this class of drugs triggers a TCR response leading to the induction of DNA damage, but whether the actions of these drugs are tumor-selective needs further evaluation.…”
Section: Targeting Dna Repair Pathwaysmentioning
confidence: 99%
“…Gemcitabine (Gem) is a pyrimidine nucleoside antimetabolite agent which is active against variety of human malignancies, including NSCLC with a favorable toxicity profile [6], [7]. Several researchers have studied the combination of Gem and cisplatin, topotecan, protease inhibitors, and ginsenoside Rg3 for the treatment of lung cancer [8], [9], [10], [11], [12]and reported enhanced anticancer effects [8], [9], [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 99%